Analisis Studi Literatur Teknik KWL dalam Peningkatan Membaca Permulaan Untuk Siswa Kelas 1 Madrasah Ibtidaiyah - Ade Dina Nurkhakiki; Dewi Nopasari (Action Research Journal, 2025)
Early reading skills are an important foundation for student literacy at the elementary school level. This study aims to examine the effectiveness of the application of the KWL (Know, Want, Learned) technique in improving the early reading skills of grade 1 students of Madrasah Ibtidaiyah. Using a literature study approach, this study analyzed various journals and scientific articles related to the application of the KWL technique. The KWL technique involves three stages, namely identifying initial knowledge (Know), determining learning objectives (Want), and reflecting on learning outcomes (Learned). The results of the study showed that the KWL technique significantly improved students' understanding of the text, learning motivation, and critical thinking skills. The use of supporting media, such as picture storybooks or letter puzzles, also strengthened the effectiveness of this technique by creating an interactive and meaningful learning experience. The application of KWL is in accordance with the theory of social constructivism and self-determination, which emphasizes the importance of social interaction and intrinsic motivation in learning. With promising results, the KWL technique can be a strategic alternative to improve students' early reading skills at the elementary school level. This study makes an important contribution to the development of innovative and enjoyable reading learning methods, which support the improvement of students' literacy quality as a whole